The Influence of Social Media on The Spiritual and Social Life of Christian Teenagers - Benny Agustinus Triangga Prayitno; Agatha Erlitawati Kaharudin (LPPM Universitas PGRI Sumatera Barat, 2024)
The use of social media in teaching Christianity is an important topic in the current digital era. This article aims to understand the impact of social media on the formation of individual spiritual identity. Social media has an important role in expanding access to information, building religious communities, and facilitating interaction between Christians. However, there are negative impacts that need to be watched out for, especially for Christian teenagers, such as reduced study time, disturbed concentration at school, decreased morale, unwise use of money, and negative impacts on health. This article advocates using social media wisely by managing time, choosing useful content, and prioritizing faith growth. A holistic approach in Christian religious education is needed to integrate spiritual values with a deep understanding of technology. Thus, the use of social media can be optimized as a means that supports spiritual growth and the formation of a strong Christian identity.